Maintaining Financial Sector Integrity: Integrating Sustainable Finance into Financial Regulation - Kukuh Komandoko Hadiwidjojo; Mikha Detalim; Mahadi Abdullah; Fayez Ghazi Mutasim Adesta (Journal of Private and Commercial Law, 2026)
This article invetigates whether the integration of sustainable finance into the Indonesian financial regulatory framework aligns with established principles of financial regulation and whether such integration strengthens or potentially undermines financial sector integrity. This study assesses Indonesia’s sustainable finance framework through a normative legal research approach. The study applies indicators derived from the principles of financial regulation, namely prudential risk integration, transparency and disclosure reliability, market integrity, supervisory effectiveness, and enforceability of sustainability-related obligations. Sustainable finance aims to incorporate environmental and social risks, especially those related to climate, into financial decision-making, but its regulatory implementation prompts significant inquiries about prudence, transparency, market integrity, and public confidence.  The research indicates that Indonesia's sustainable finance governance faces three critical challenges: legitimacy risks stemming from vague green product classifications that enable greenwashing and erode trust, reputational risks caused by a lack of rigorous verification and mispricing concerns. Additional shortcomings include weak verification mechanisms for sustainability claims and the risk of symbolic compliance without substantive integration into prudential supervision. The research further finds that sustainable finance has a dual nature: when firmly rooted in legal authority, incorporated into prudential oversight, backed by uniform disclosure frameworks, and upheld through reliable supervisory systems, it boosts systemic resilience and strengthens regulatory legitimacy. On the other hand, disjointed execution, lax verification criteria, symbolic compliance, and inadequate enforcement can lead to greenwashing, regulatory arbitrage, mispricing, and reputational spillover, thereby threatening reputation of financial sector. The research finds that the effectiveness of sustainable finance in Indonesia relies on careful regulatory frameworks, strong institutional capabilities, and efficient enforcement to maintain the integrity of the financial sector.